Pharmacological profile of the novel potent antirheumatic 4-(2',4'-difluorobiphenyl-4-yl)-2-methyl-4-oxobutanoic acid - Panajotova, V; Andĕrova, E; Jandera, A; Kuchar, M (Arzneimittel-Forschung, 1997)
On the basis of basic screening for novel, more potent antiarthritics VUFB-16066 (4-(2',4'-difluorobiphenyl-4-yl)-2-methyl-4-oxobutanoic acid, CAS 112344-S2-2) was chosen as a compound with pronounced anti-inflammatory and immunomodulatory effects, with good gastric tolerance and relatively low toxicity. VUFB-16066 is a dual cyclooxygenase and 5-lipoxygenase inhibitor, and it suppresses alloantigen-driven cellular immune response and phagocytosis of stimulated peritoneal cells. VUFB-16066 exhibits prolonged pharmacological activity connected with its major metabolite having a very long half-life. In the model of adjuvant arthritis VUFB-16066 improves most of disease symptoms including immunopathological disturbances, which indicates possible disease-modifying activity of the drug. The beneficial antiarthritic effect of VUFB-16066 has been also confirmed in patients with rheumatoid arthritis.
Keywords: kyselina octová; reakce štěpu proti hostiteli; Animals; pleuritida; potkani inbrední LEW; antiflogistika nesteroidní; Abdominal Pain; Arachidonic Acid; Female; Graft vs Host Reaction; butyráty; kyselina arachidonová; ženské pohlaví; edém; diklofenak; Pleurisy; Dinoprostone; žaludeční vředy; Butyrates; dinoproston; Mice; myši; Phenylbutyrates; Anti-Inflammatory Agents, Non-Steroidal; karagenan; bolesti břicha; Arthritis, Experimental; Male; Acetic Acid; Diclofenac; fagocytóza; Phagocytosis; leukotrien B4; krysa rodu Rattus; Carrageenan; zvířata; mužské pohlaví; Leukotriene B4; artritida experimentální; Mice, Inbred C57BL; Edema; fenylbutyráty; Rats; Rats, Inbred Lew; Stomach Ulcer; myši inbrední C57BL